2016
DOI: 10.3171/2016.7.focus16191
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocephalus: the role of cerebral aquaporin-4 channels and computational modeling considerations of cerebrospinal fluid

Abstract: Aquaporin-4 (AQP4) channels play an important role in brain water homeostasis. Water transport across plasma membranes has a critical role in brain water exchange of the normal and the diseased brain. AQP4 channels are implicated in the pathophysiology of hydrocephalus, a disease of water imbalance that leads to CSF accumulation in the ventricular system. Many molecular aspects of fluid exchange during hydrocephalus have yet to be firmly elucidated, but review of the literature suggests that modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 137 publications
0
36
0
Order By: Relevance
“…However, another group of studies has shown that the role of cerebrospinal fluid (CSF) hydrodynamics is highly prominent in managing many diseases associated with the CSF circulation system 21,[33][34][35][36][37][38] . Hydrodynamic studies of CSF have shown that the incidence of CM-I is accompanied by changes in hydrodynamic parameters of CSF flow 21,[39][40][41][42][43][44][45][46] .…”
mentioning
confidence: 99%
“…However, another group of studies has shown that the role of cerebrospinal fluid (CSF) hydrodynamics is highly prominent in managing many diseases associated with the CSF circulation system 21,[33][34][35][36][37][38] . Hydrodynamic studies of CSF have shown that the incidence of CM-I is accompanied by changes in hydrodynamic parameters of CSF flow 21,[39][40][41][42][43][44][45][46] .…”
mentioning
confidence: 99%
“…Moreover, in congenital hydrocephalus patients, the cerebrospinal fluid also shows a higher AQP4 expression [ 13 ]. A variety of studies show that the AQP4 level in cerebrospinal fluid and parenchyma of subjects with hydrocephalus is elevated, and this disturbance is correlated with hydrocephalus severity [ 13 , 14 , 16 ]. This suggests that AQP4 has a relationship with hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Further data suggest that aquaporin-4 channels can be implicated in the pathophysiology of iNPH [31]. Aquaporin-4 channels are transmembrane proteins that facilitate water transport in the brain and play roles in fluid secretion, cell migration, brain edema, metabolism, and many aspects of cell homeostasis; a modulation of their activity could be a potential target for pharmacological management of iNPH.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…In patients who are poor candidates for shunt surgery, repeated lumbar punctures in combination with acetazolamide may be considered [45]. Recent studies on aquaporin-4 channels suggest interesting perspectives for future pharmacological treatment of iNPH [31].…”
Section: Managementmentioning
confidence: 99%